Performance of some jute & allied fiber varieties in the southern part of Bangladesh - Islam, Md.Monirul; Islam, Mohammad Kabirul; Hoque, Md.Fazlul; Bhuyan, Md.Isfatuzzaman; Islam, Md.Sazedul; Hassan, K.M.Mehadi; Ferdous, Mahbuba (International Journal of Advanced Geosciences, 2018)
The present study was conducted to know the performance of growth, yield contributing parameters and yield of some Tossa and Deshi Jute and also some Allied fiber varieties at the agronomy field laboratory during the period from March to September 2012. Twelve Jute and Kenaf vareities viz. CVL–1 (V1), HC–2 (V2), 0–9897 (V3), CVE–3 (V4), 0–72 (V5), BJC–7370 (V6), HC–95 (V7), BJC–83 (V8), VM–1 (V9), 0–795 (V10), HC–3 (V11), BJC–2142 (V12) were taken and catagorized into three viz. Deshi (V1 to T5), Tossa (V6 to V8) and Kenaf (V9 to V12). The single factor experimental data was laid out in a completely randomized block design with three replications and the means were adjudged by DMRT at 5% level of probability. Varietals performance of Jute and Kenaf were showed statistically significant variation among the studied whole growth, yield and yield attributing traits. Among the varieites, the Jute variety BJC–7370 porduce the tallest plant (299.0 cm), medium base diameter (27.04) mm and longest root (28.44 cm) at harvest. Dry matter viz. root (13.51 g plant–1), stem (48.51 g plant–1), leaf (12.87 g plant–1) and TDM (74.89 g plant–1) production had also higher in BJC–7370. However, base diameter (26.84 mm) and dry weight of leaf (12.37 g plant–1) were statistically similar with Kenaf variety HC–3. The Jute variety BJC–7370 had also showed greater results on various yield characters viz. green (whole plant) weight (232.4 g plant–1) and stick (58.97 g plant–1) and fiber yield (58.97 g plant–1).The Kenaf variety HC–3 was also showed fiber (19.91 g plant–1) production. So, therefore, the Jute variety BJC–7370 and Kenaf vareity HC–3 gave understanding superiority on growth, yield and yield contributing traits as well as higher seed and fiber yield under the AEZ–13. So, Jute variety BJC–7370 or Kenaf variety HC–3 would be more successful productive variety in AEZ– 13 compare to the other studied Jute and Allied fiber varieties.